2006
DOI: 10.1111/j.1440-1614.2006.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for cannabis use in psychosis

Abstract: Objective: To examine the reasons for cannabis use among individuals with psychotic disorders. Method: Forty-nine people with psychotic disorders in treatment with community health centres in Northern Sydney were interviewed to collect information about their experience of antipsychotic side-effects and their influence on cannabis use. Other information collected on cannabis use included: amount and frequency, effects of use and other general reasons given for use. Results: It was found that boredom, social mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 12 publications
4
42
0
Order By: Relevance
“…Five studies were conducted in Australia [22,26,29,31,33] , 5 in the USA [23-25, 27, 30] , 1 in Canada [28] , 1 in India [32] , 1 in Germany [34] and 1 in Spain [35] . One study compared reasons for and effects of cannabis use in individuals with and without psychosis, within a single study [22] .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in Australia [22,26,29,31,33] , 5 in the USA [23-25, 27, 30] , 1 in Canada [28] , 1 in India [32] , 1 in Germany [34] and 1 in Spain [35] . One study compared reasons for and effects of cannabis use in individuals with and without psychosis, within a single study [22] .…”
Section: Resultsmentioning
confidence: 99%
“…The first study to make a comprehensive examination of subjective experiences of cannabis use and reasons for using the drug among a group of people with psychosis found that the primary reason given was related to neither positive or negative symptoms, nor obvious side-effects of medication (Schofield et al, 2006). Instead, the most frequently cited motivations were to reduce boredom, improve socialisation and alleviate a cluster of symptoms, the most common of which were inner unrest/agitation (47%) and difficulty sleeping (43%).…”
Section: What Do Researchers Say?mentioning
confidence: 99%
“…Reasons like these give voice to those who use marijuana to selfmedicate their psychosis Schofield et al 2006). The correlation between psychosis and regular cannabis use is concerning enough (Os et al 2002;Ruiz-Veguilla et al 2013), but several reasons compound our alarm.…”
Section: A Virtue Analysis Of Recreational Marijuana Usementioning
confidence: 99%